Single flake homo p–n diode of MoTe2 enabled by oxygen plasma doping - Zulfiqar Irsa; Gul Sania; Sohail Hafiz Aamir; Rabani Iqra; Gul Saima; Rehman Malik Abdul; Wabaidur Saikh Mohammad; Yasir Muhammad; Ullah Inam; Khan Muhammad Asghar; Rehman Shania; Khan Muhammad Farooq (Nanotechnology Reviews, 2024)
Two-dimensional (2D) materials play a crucial role as fundamental electrical components in modern electronics and optoelectronics next-generation artificial intelligent devices. This study presents a methodology for creating a laterally uniform p–n junction by using a partial oxygen plasma-mediated strategy to introduce p-type doping in single channel MoTe2 device. The MoTe2 field effect transistors (FETs) show high electron mobility of about ∼23.54 cm2 V−1 s−1 and a current ON/OFF ratio of ∼106 while p-type FETs show hole mobility of about ∼9.25 cm2 V−1 s−1 and current ON/OFF ratio ∼105 along with artificially created lateral MoTe2 p–n junction, exhibited a rectification ratio of ∼102 and ideality factor of ∼1.7 which is proximity to ideal-like diode. Thus, our study showed a diversity in the development of low-power nanoelectronics of next-generation integrated circuits.